AN OUTLINE OF ALTERNATIVE AVIATION FUELS FROM SUSTAINABLE RESOURCES (Jurnal Teknologi (Sciences & Engineering), 2022)
The depletion of fossil fuels and their market inequality have led to the popularity of biofuels. Biofuels are a renewable energy source which can be a promising solution to the environmental issues created by fossil fuels. The emission of greenhouse gases and fluctuating prices of fossil fuels have put pressure on developing countries and small economic nations. Thus, one of the main concerns is the production of bio jet fuel from renewable resources, with a relatively low greenhouse gas life cycle and sustainability with affordable prices. Therefore, it is imperative to introduce and produce alternative aviation fuels generated from sustainable resources, specifically biofuels. In this study, we have reviewed alternative aviation fuels and their sources. We have also outlined the selection criteria for alternative aviation fuels along with discussing the sources that can be potentially used as fuel for the aviation industry.